Diversidade da Flora Apícola em uma região do Bioma Pampa: Uma Abordagem Integrada entre Palinologia e DNA metabarcoding - Novaes , Flávia Santos Vieira (2025)
Beekeeping is a highly relevant agricultural activity with a recognized socio-economic, socio-cultural and socio-environmental role. In addition to producing products such as honey, propolis and wax, bees perform a crucial ecosystem service: pollination of agricultural crops and natural environments. In Brazil, this practice has been growing more and more, especially in Rio Grande do Sul, which has been one of the main honey-producing states for more than a decade. However, despite the recognized importance of bees, the predatory dynamics of land use, with the widespread suppression of native vegetation, represent a constant threat to the health and survival of these pollinators. In this context, studying the native flora used by bees is an essential step towards planning sustainable beekeeping practices that favor pollinator health and plant conservation in production areas. To this purpose, this study investigated, by analyzing bee pollen, which native species in a region of the Brazilian Pampa Biome have the potential to be used in beekeeping areas and how their flowers are distributed throughout the year. Corbicular pollen was collected every two weeks from four hives over the course of a year (November 2023 to October 2024), as well as from fertile plants around the apiary. The reference palynological laminarium was drawn up from the pollen collected from the flowers. The corbicular pollen was identified through palynological analysis of slides with acetolyzed material and molecular analysis using the DNA-metabarcoding technique. In addition, the abundance and richness of species over the months was assessed. After a year of collecting, 58 plants foraged by Apis mellifera were detected, of which 46 were identified to species level, 33 of which were native. The abundance and richness data showed significant variations throughout the year, with the highest values concentrated in the months of August to December, followed by a peak in March. The most common pollen types were Eugenia uniflora, Eucalyptus sp., Senecio brasiliensis and Solidago chilensis. With regard to the metabarcoding results, there was a greater overlap with the palynology data when the analysis was carried out against a library prepared from these results. The results indicate that palynological analysis is still the most reliable method for detecting the botanical origin of products from regions where the genetic diversity of the vegetation is not fully represented in databases. The diversity of native plants from the Brazilian Pampa Biome used by Apis mellifera shows their potential to supply bee forage. These data contribute both to the palynology of bee species and to complementing environmental conservation studies, as well as aiding the development of sustainable beekeeping management strategies in the region.